2012
DOI: 10.1097/olq.0b013e31826ae875
|View full text |Cite
|
Sign up to set email alerts
|

Trichomonas vaginalis Prevalence Increases With Remoteness in Rural and Remote New South Wales, Australia

Abstract: The prevalence of Trichomonas was relatively high among women attending sexual health clinics in rural and remote western New South Wales. Trichomonas was more common among women living more remotely, which may reflect population-level health service use. Testing for Trichomonas should be considered for all women requesting testing for sexually transmitted infections in rural and remote Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
0
9
1
Order By: Relevance
“…21,22,25–27 Our study, however, showed a similar prevalence with the 18.7% recorded in Zaria, 19 but a lower prevalence than the 24.1% observed in Jos. 28 Compared with the rest of the world, our study showed a higher prevalence than the values reported in Iran (3.3%), Turkey (12.3%) and the Australian aboriginal population (8.4%), 2931 but lower than the prevalences of 24.7%, 34.0% and 49.2% reported in Tanzania, 32 Kenya 33 and South Africa, 34 respectively. This prevalence suggests that maternal T. vaginalis infection is an important public health threat in Nigerian urban populations.…”
Section: Discussioncontrasting
confidence: 45%
“…21,22,25–27 Our study, however, showed a similar prevalence with the 18.7% recorded in Zaria, 19 but a lower prevalence than the 24.1% observed in Jos. 28 Compared with the rest of the world, our study showed a higher prevalence than the values reported in Iran (3.3%), Turkey (12.3%) and the Australian aboriginal population (8.4%), 2931 but lower than the prevalences of 24.7%, 34.0% and 49.2% reported in Tanzania, 32 Kenya 33 and South Africa, 34 respectively. This prevalence suggests that maternal T. vaginalis infection is an important public health threat in Nigerian urban populations.…”
Section: Discussioncontrasting
confidence: 45%
“…Therefore, TV positivity could have been underestimated, since many overseas countries have higher TV prevalence than Australia 4 . Finally, our findings are unlikely to be generalisable to rural and remote Australian settings, where TV prevalence is higher and disproportionately affects Aboriginal communities 7–9 …”
Section: Discussionmentioning
confidence: 81%
“…Nucleic acid amplification tests (NAAT) are more sensitive than wet‐film 4 microscopy and are the optimal diagnostic method in developed countries 1 . Among Australian women, reported NAAT‐diagnosed prevalence varies widely (0.38–8.4%) 5–9 . Our aim was to assess whether routine NAAT testing for genital TV in females is indicated in an urban Australian setting.…”
mentioning
confidence: 99%
“…Considering the Asian continent, consistent survey reports revealed prevalence values of 7.8% in South Korea 41 and 8.5% in India 42. Trichomoniasis prevalence varied from 8.4% to 48% among Indigenous patients in Australia 4344. The Nordic countries in Europe account with 1.5% for the trichomoniasis prevalence 45 and in South Africa the prevalence was 6.5%, excluding co-infection cases with HIV 46.…”
Section: Trichomoniasis In Numbersmentioning
confidence: 80%